Cheating among health sciences students forms, attitudes and perceived prevalence - Griño, Maria Monica S.
Upholding the culture of academic integrity is a fundamental role of health science institutions. As previous researches indicate that students who cheat are likely to engage in professional misconduct, cheating should be abhorred, more so in schools teaching future health professionals, who will be responsible for society's health and people's lives. This study was conducted to 1) identify activities, scenarios and situations perceived by students as forms of cheating; 2) describe the students' attitude toward cheating; 3) determine the perceived prevalence of cheating among students; 4) determine the association between the attitude toward cheating and cheating behavior; 5) describe the association of the following factors, namely, sex, year level, general weighted average (GWA), home college, and membership in student organization with students' perceived forms of cheating, attitude toward cheating and prevalence of cheating, 6) determine which factors predict students' attitude towards cheating, and 7) determine which factors predict cheating behaviors. Using a cross-sectional survey, 462 health sciences students from the 3rd and 4th year levels of the Colleges of Allied Medical Professions, Dentistry, Nursing, Pharmacy, and Public Health of the University of the Philippines Manila were surveyed. More than 87% perceived test or examination-related behaviors as cheating while more than 67% perceived paper-related behaviors as cheating. Students show a conservative attitude towards cheating where 75% believes that cheating is bad, more than 65% has negative feelings on cheating and more than 60% will not cheat despite the circumstance. Cheating is prevalent among the five health colleges with 87.7% of the respondents participated in any one form of cheating. The most prevalent forms of cheating according to self-reports are: Allowing someone to copy your homework (72.3%), Using an old test to study without the teacher's knowledge (50.9%), ?Copy and paste? sections of articles from internet sites (47.8%), Doing projects outside course hours which are supposed to be done in class (40.9%) and Not citing references for ideas taken in other articles or papers (30.1%). Students show a conservative attitude towards cheating, however, majority of students who have conservative and liberal attitude similarly engaged in cheating. Cheating behavior cannot be directly associated with attitude towards cheating (ATC) despite the multi-compartment analysis of attitude. Among the individual factors, only sex, year level and home college affect students' perceptions of cheating behaviors. Only sex and home college seem to affect attitude toward, while sex, year level, GWA and home college affect prevalence of cheating. Membership in student organization is not a factor affecting perception and attitude toward cheating and participation in cheating behaviors. Logistic regression analysis showed that students with high GWA have a more conservative ATC while members of student organizations have a more liberal ATC. Moreover, females with high GWA and those coming from the College of Pharmacy are more likely to engage in cheating. Results of the study can be utilized to create mechanisms to identify possible student offenders, promote measures to instill classroom discipline and ethics, and create reforms in institutions to deter academic cheating.